Eomes Impedes Durable Response to Tumor Immunotherapy by Inhibiting Stemness, Tissue Residency, and Promoting the Dysfunctional State of Intratumoral CD8+ T Cells - Sun, Runzi; Wu, Yixian; Zhou, Huijun; Wu, Yanshi; Yang, Zhongzhou; Gu, Yanzheng; Jiang, Jingting; Lu, Binfeng; Zhu, Yibei (Frontiers in Cell and Developmental Biology, 2021)
Sustaining efficacious T cell-mediated antitumor immune responses in the tumor tissues is the key to the success of cancer immunotherapy. Current strategies leverage altering the signals T cells sense in the tumor microenvironment (TME). Checkpoint inhibitor-based approaches block inhibitory signals such as PD-1 whereas cytokine-based therapies increase the level of immune-stimulatory cytokines such as IL-2. Besides extrinsic signals, the genetic circuit within T cells also participates in determining the nature and trajectory of antitumor immune responses. Here, we showed that efficacy of the IL33-based tumor immunotherapy was greatly enhanced in mice with T cell-specific Eomes deficiency. Mechanistically, we demonstrated that Eomes deficient mice had diminished proportions of exhausted/dysfunctional CD8+ T cells but increased percentages of tissue resident and stem-like CD8+ T cells in the TME. In addition, the IFNg+TCF1+ CD8+ T cell subset was markedly increased in the Eomes deficient mice. We further demonstrated that Eomes bound directly to the transcription regulatory regions of exhaustion and tissue residency genes. In contrast to its role in inhibiting T cell immune responses at the tumor site, Eomes promoted generation of central memory T cells in the peripheral lymphoid system and memory recall responses against tumor growth at a distal tissue site. Finally, we showed that Eomes deficiency in T cells also resulted in increased efficacy of PD-1-blockade tumor immunotherapy. In all, our study indicates that Eomes plays a critical role in restricting prolonged T cell-mediated antitumor immune responses in the TME whereas promoting adaptive immunity in peripheral lymphoid organs.